2011
DOI: 10.1259/bjr/43400531
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of contrast-enhanced ultrasound in the detection of bladder cancer

Abstract: Objective: To assess the accuracy contrast-enhanced ultrasound (CEUS) in bladder cancer detection using transurethral biopsy in conventional cystoscopy as the reference standard and to determine whether CEUS improves the bladder cancer detection rate of baseline ultrasound. Methods: 43 patients with suspected bladder cancer underwent conventional cystoscopy with transurethral biopsy of the suspicious lesions. 64 bladder cancers were confirmed in 33 out of 43 patients. Baseline ultrasound and CEUS were performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
38
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 32 publications
(42 reference statements)
0
38
0
2
Order By: Relevance
“…In addition, the excretory phase is not the only phase in which urothelial cell carcinoma can be detected. Urothelial cell carcinoma becomes enhanced soon after contrast administration [6][7][8] and can be detected in the corticomedullary or nephrographic phase or if the urinary tract, including the bladder, is well distended with urine, which acts as a negative contrast medium.…”
Section: Dose Saving In Ct Urographymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the excretory phase is not the only phase in which urothelial cell carcinoma can be detected. Urothelial cell carcinoma becomes enhanced soon after contrast administration [6][7][8] and can be detected in the corticomedullary or nephrographic phase or if the urinary tract, including the bladder, is well distended with urine, which acts as a negative contrast medium.…”
Section: Dose Saving In Ct Urographymentioning
confidence: 99%
“…When focus in recent years turned to urothelial cell carcinoma, the corticomedullary phase proved useful in detecting urothelial cell carcinoma in the upper urinary tract and bladder. Several reports describe urothelial cell carcinoma as strongly enhancing with contrast material [6][7][8] in the early phase after contrast administration. A prospective study with patients undergoing workup because of gross hematuria was performed with an unenhanced, corticomedullary, nephrographic, and excretory phase protocol.…”
Section: Dose Saving In Ct Urographymentioning
confidence: 99%
“…It has been demonstrated that CEUS improves the differential diagnosis of intraluminal masses, allowing the differentiation between tumors, which are vascularized and show enhancement, and clots, which do not enhance [4][5][6]. CEUS also resulted to be superior to grayscale ultrasound in assessing infiltration of the muscle wall-layer, but magnetic resonance imaging (MRI) and computed tomography (CT) remain the imaging modalities of choice for local staging of bladder tumors [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Contrast-enhanced MRI has been applied, but it is expensive and bulky [1]. Although ultrasound (US) imaging is real-time, portable, relatively cost effective, and safe, conventional US imaging is not sensitive, especially, for imaging bladder cancers [2].…”
mentioning
confidence: 99%